Indirect Selection on Flower Color in Silene littorea - Rodríguez-Castañeda, Nancy L.; Ortiz, Pedro L.; Arista, Montserrat; Narbona, Eduardo; Buide, Mª Luisa (Frontiers in Plant Science, 2020)
Flower colour, as other floral traits, may suffer conflicting selective pressures mediated by both mutualists and antagonists. The maintenance of intraspecific flower colour variability has been usually explained as a result of direct selection by biotic agents. However, flower colour might also be under indirect selection through correlated traits, since correlations among flower traits are frequent. In this study, we aimed to find out how flower colour variability is maintained in two nearby populations of Silene littorea that consistently differ in the proportions of white-flowered plants. To do that, we assessed natural selection on floral colour and correlated traits by means of phenotypic selection analysis and path analysis. Strong directional selection on floral display and flower production was found in both populations through either male or female fitness. Flower colour had a negative indirect effect on total male and female fitness in Melide population, as plants with lighter corollas produced more flowers. In contrast, in Barra population, plants with darker corollas produced more flowers and have darker calices, which in turn were selected. Our results suggest that the prevalence of white-flowered plants in Melide and pink-flowered plants in Barra is a result of indirect selection through correlated flower traits, and not a result of direct selection of either pollinators or herbivores on colour.